2023
DOI: 10.1021/acs.jpcb.2c08625
|View full text |Cite
|
Sign up to set email alerts
|

Evolution, Stability, and Applicability of Surfactant Aggregates in Targeted Delivery

Abstract: Self-assembly/self-aggregation of surfactant molecules in bulk and the vicinity of a surface has been a topic of interest for decades because of its utilization in numerous modern technical applications. In this article, the results of molecular dynamics simulations are reported to investigate the self-aggregation of sodium dodecyl sulfate (SDS) at an interface of mica and water. SDS molecules starting from lower to higher surface concentrations tend to create distinct aggregated structures in the vicinity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
(115 reference statements)
0
1
0
Order By: Relevance
“…The conformational stability and structural integrity of the protein are very sensitive to the surrounding environment, i.e., a medium where the protein is being stored or transported. Therefore, by tuning the physicochemical properties of the stabilizing medium, such as polymers, amino acids, and/or osmolytes, the function of the protein can be altered. Although literature reports provide limited results on the stabilization of proteins and/or peptides even in the presence of conventional surfactants such as SDS, , this approach has received limited applications. As the opportunity to change the physicochemical properties of these stabilizers is limited and several studies have shown that these stabilizers are not suitable for the long-term preservation of proteins, the development of new formulations for protein is needed …”
Section: Introductionmentioning
confidence: 99%
“…The conformational stability and structural integrity of the protein are very sensitive to the surrounding environment, i.e., a medium where the protein is being stored or transported. Therefore, by tuning the physicochemical properties of the stabilizing medium, such as polymers, amino acids, and/or osmolytes, the function of the protein can be altered. Although literature reports provide limited results on the stabilization of proteins and/or peptides even in the presence of conventional surfactants such as SDS, , this approach has received limited applications. As the opportunity to change the physicochemical properties of these stabilizers is limited and several studies have shown that these stabilizers are not suitable for the long-term preservation of proteins, the development of new formulations for protein is needed …”
Section: Introductionmentioning
confidence: 99%
“…The SAM formation at a solid–liquid interface happens due to either physisorption driven by weak van der Waals and cohesive interactions, or chemisorption due to either strong electrostatic interactions, or strong affinity between the solid surface and the molecules, like intramolecular hydrogen bonding . Self-assembled structures at an interface, especially solid–liquid, are changed owing to the intrinsic heterogeneity of the interface, depending mainly on hydrophilicity, and the crystallographic plane of the surface, and based on that, they can further influence the properties of any surface like preventing oxidation, enhanced hydrophobicity, , improved adhesion, facilitation of molecular and biological recognition processes, etc. , Self-assembly of amphiphiles, including surfactants, alkanols, thiols, and other similar compounds, are investigated in solutions or at a solid–liquid interface using computational microscopy , and experiments. , Self-assemblies of these amphiphiles are notably influenced by the water layer adhering to the hydrophilic surfaces, particularly for the surfactants. In contrast, in the case of hydrophobic surfaces, the strong, cohesive interactions come into contention, depending on the surface coverages of the molecules. , The chain length of the molecules is also a crucial factor in governing the structural behaviors of the adsorbed monolayers. , Longer chains promote enhanced molecular packing and ordering within the monolayers, leading to more well-defined and organized structures .…”
Section: Introductionmentioning
confidence: 99%